2019
DOI: 10.1002/jcb.29510
|View full text |Cite
|
Sign up to set email alerts
|

LINC00467 promotes cell proliferation and stemness in lung adenocarcinoma by sponging miR‐4779 and miR‐7978

Abstract: Lung adenocarcinoma (LAD), as one of the most common types of lung tumors, is lethal and malignant. Long noncoding RNAs (lncRNAs) play important roles in various cancers according to many previous studies. LINC00467 was proposed to be a tumor promoter. Despite the validated promotive effect of LINC00467 on neuroblastoma progression, its regulatory mechanism in LAD remains unclear. In this study, LINC00467 expressed higher in LAD tissues and cell lines, and increased LINC00467 indicated a poor prognosis. Knockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Research regarding linc00467 outside the digestive system in malignant tumors mainly focused on lung cancer and glioma. It was also demonstrated that the expression of linc00467 was elevated in lung adenocarcinoma tissues and cell lines, involved in tumorigenesis [ 20 , 28 , 29 ]. Several initiated signaling pathways, including linc00467/miR-20b-5p/cyclin D1 pathway [ 20 ] and STAT1-induced upregulation of linc00467 promoted lung adenocarcinoma progression through epigenetically suppressing dickkopf WNT signaling pathway inhibitor 1 to activate Wnt/β-catenin signaling [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research regarding linc00467 outside the digestive system in malignant tumors mainly focused on lung cancer and glioma. It was also demonstrated that the expression of linc00467 was elevated in lung adenocarcinoma tissues and cell lines, involved in tumorigenesis [ 20 , 28 , 29 ]. Several initiated signaling pathways, including linc00467/miR-20b-5p/cyclin D1 pathway [ 20 ] and STAT1-induced upregulation of linc00467 promoted lung adenocarcinoma progression through epigenetically suppressing dickkopf WNT signaling pathway inhibitor 1 to activate Wnt/β-catenin signaling [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several studies have reported that LINC00467 may serve as a promotor in LUAD ( 17 21 ). All these studies have suggested that LINC00467 expression is elevated in both patients and LUAD cell lines and that increased LINC00467 expression indicates a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is altered in several cancer types, including both solid tumors (9)(10)(11)(12)(13)(14)(15) and hematologic malignancies (16). In LUAD, LINC00467 expression has been reported to be upregulated, and its high expression contributes to tumorigenesis by promoting cell proliferation or stemness (17)(18)(19)(20)(21). However, the mechanism underlying its abnormal upregulation and its prognostic significance in LUAD remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite it has been previously reported the oncogenic role in multiple cancer types (14)(15)(16)18), the expression pattern and functional mechanism of LINC00467 in breast cancer has never been investigated. In the current study, we firstly reported that LINC00467 promoted proliferation, migration, invasion and EMT of breast cancer cells in vitro as well as tumor growth and lung metastasis in Balb/c nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it was also reported that LINC00467 expression was associated with Vogt-Koyanagi-Harada Disease and Behcet's Disease (13). Numerous studies indicated LINC00467 acted as an oncogene in colorectal cancer, lung adenocarcinoma, hepatocellular carcinoma, glioma, head and neck squamous cell carcinoma and acute myeloid leukemia (14)(15)(16)(17)(18)(19). Nevertheless, the expression pattern and functional role of LINC00467 in breast cancer has been less explored.…”
Section: Introductionmentioning
confidence: 99%